The rise and decline of party activism in South Africa - Stadler, Alfred William (My University, 1997)
This paper is concerned to identify the decline in party activism in South Africa since before the general election of 1994. The paper falls into three parts: a brief overview of the general literature on the problem, including references to developments in post-colonial Africa; a schematic account of political activism in black politics in South Africa since the end of the second world war; and thirdly a series of cases in local politics in Mpumalanga at the time of the local elections of 1996 which suggest that there are areas where local party and social movement activism is still visible in the form of internal conflicts, or conflicts between the ANC and its allies, notably SANCO. These cases will be used to show the sometimes complex relations in local politics, and specifically the varied consequences of institutionalising democracy at the local level. The theoretical starting point lies in the debates which followed Oscar Kirchheimer's famous prediction that the "mass integration" class-based party which had politicised the European peasantry and working class in an earlier period, had gone into decline after the second world war, and was being displaced by the "catch-all party". (1) Kirchheimer argued that the catch-all party abandoned all efforts "at the intellectual and moral encadrement of the masses,... turning more fully to the electoral scene, trying to exchange effectiveness in depth for a wider audience and more immediate electoral success. The narrower political task and the immediate electoral goal differ sharply from the former allembracing concerns..." (2)
African Studies Seminar series. Paper presented 6 October 1997
Keywords: African National Congress; Political parties. South Africa. History, 20th century